Review Artikel : Potensi Zingiberaceae Sebagai Nutraceutical Pada Budidaya Ikan - Viki Mustofa; Nur Saidah Said; Deka Uli Fahrodi; Hendro Sukoco (Samakia : Jurnal Ilmu Perikanan, 2022)
Nutraceuticals for fish that have potential in Indonesia are plants of the Zingiberaceae family which contain many essential oils, including terpenes, alcohols, ketones, flavonoids, carotenoids, and phytoestrogens. This review article aims to provide scientific information about Zingiberaceae with nutraceutical phytochemical activity as well as information about effects on the immune system and growth performance for aquaculture. The method used is a literature study from several scientific publications in national and international journals about the potential of Zingiberaceae as an immunostimulant and growth promoter in fish. Several studies have shown that the Zingiberaceae family has potential as a nutraceutical in aquaculture because Zingiberaceae contains very diverse bioactive compounds, such as alkaloids, saponins, tannins, coumarins, flavonoids, diterpenes, phlobatannins, cardiac glycosides, phenols, steroids, anthraquinones, reducing sugars, anthocyanins. , terpenoids, Essential oils (sabinine, borneol, α-phellandrene, cineol, sesquiterpines, zingiberene, curcumin (diferuloyl methane) gingerols, shogaols, paradols which have antioxidant, anti-inflammatory, and antimicrobial properties. In addition, they can be used to promote growth, feed efficiency, immune response enhancement, treatment and prevention of several fish diseases caused by infectious agents.